Determination of plasma albumin concentration in healthy and diseased turtles a comparison of protein electrophoresis and the bromcresol green dye-binding method - Müller, Kerstin (Veterinary clinical pathology, 2010)
BACKGROUND: In reptile medicine, plasma chemistry analysis is widely used for the evaluation of an individual's health status. The standard method for the determination of plasma albumin concentration is protein electrophoresis combined with the determination of total protein concentration, but the bromcresol green (BCG) dye-binding method is also used. The reliability of the BCG method for the measurement of albumin concentration in reptiles is unknown